Sosialisasi Sampah Melalui Bank Sampah untuk Menyejahterakan Masyarakat di Desa Truko Jawa Tengah - Siregar, Hajizah Azmi; Siregar, Noya Yukari; Selfia, Yeni (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Indonesia is the second largest contributor to plastic waste after China. In this case, the Kendal Regency government has various ways to educate the community to be aware of the importance of waste management. One way to reduce the amount of waste is by establishing Garbage Bank. Truko Village is one of the villages in Kendal district, Central Java province, this village was selected for community service activities because Truko village does not yet have a Garbage Bankand the village community also does not understand the system of running a Garbage Bank. This happens because there is still a lack of information about the Garbage Bank and proper waste management. To achieve this goal, the methods used are:1) Educating the public about the Garbage Bank program 2) Socializing the management of Garbage Bank and waste 3) Socialization and training on waste management has become a valuable project. The existence of this article is expected to improve facilities in Truko village and in other villages with a plan to form a Waste Bank.Establishing a Garbage Bank is a way to improve village facilities because with a Garbage Bank the waste management process will be more focused, it is hoped that this article can provide information to people in Truko Village and people outside Truko Village the process of forming a Garbage Bank and managing waste appropriately to become valuable goods selling